Sistem Informasi Monitoring Pengiriman Kargo DAMRI Logistik Lintas Jawa - Sumatera Berbasis Web - Abimanyu, Chaidar; Sudarsono, Bernadus Gunawan; Whendasmoro, Raditya Galih (Eksplorasi Teknologi Enterprise dan Sistem Informasi (EKSTENSI), 2023)
Cargo delivery is an integral part of logistics operations, where monitoring plays a crucial role. Manual approaches in monitoring increase the risk of human error and prolong the process duration. Major issues frequently encountered in cargo delivery, such as damages, losses, and bus travel delays, can be addressed through the implementation of monitoring systems. Damages and losses during cargo transportation, coupled with significant bus travel delays, stem from finalizing cargo delivery data after passenger check-in. This research aims to identify the root causes of these three issues and offer solution recommendations to enhance the reliability of the cargo delivery process. The research methodology includes analysis of historical delivery data, interviews with operational crews, and the development of a web-based information system for more structured monitoring processes. Research findings indicate that discrepancies between delivery schedules and inconsistent monitoring are primary factors contributing to damages, losses, and delays. Recommended solutions involve implementing real-time tracking systems and providing training to enhance awareness of swift and accurate delivery procedures. In conclusion, understanding the challenges encountered in cargo delivery can contribute to developing better service solutions, thereby improving overall logistics efficiency within DAMRI logistics.